Conjugated linoleic acid content and fatty acids profile of milk from grazing dairy cows in southern Chile fed varying amounts of concentrate. Issue 1 (1st January 2018) - Marín, M. P.; Meléndez, P. G.; Aranda, P.; Ríos, C.
ABSTRACT: Conjugated linoleic acids (CLAs) are fatty acids found in bovine milk which possess benefits for human health. This study aimed to compare fatty acid profiles, particularly CLA, of milk from grazing cows from south Chile receiving varying levels of concentrate. The study was conducted during spring of 2012 in two dairies from southern Chile. Dairy A was under low grazing intensity with high levels of concentrate (6–8 kg/cow/day); Dairy B combined low levels of concentrate (1–2 kg/cow/day) with more intensive grazing activity. Milk and blood samples were collected from 15 cows at each dairy at 30 days postpartum. Milk was analysed for fatty acid profiles, and blood for beta-hydroxybutyrate. Body condition score, parity, and daily milk yields were recorded. Pasture and concentrates were sampled for nutritional analysis. The proportion of CLA isomers in milk was 0.91% and 1.66% for Dairy A and Dairy B, respectively ( p < .05). Dairy B had a lower ratio of saturated to unsaturated fatty acid and higher levels of omega-3 fatty acids than Dairy A. In conclusion, cows with increased grazing and low concentrate presented higher levels of CLA and omega-3 fatty acids than cows with less grazing and greater concentrate.